Pakarena di Sulawesi Selatan: Dari tarian tradisional ke neo-tradisonal / Anggrawansyah Syaharuddin - Anggrawansyah, Syaharuddin (2017)
This research is based on the comparison between two dances, namely, Pakarena traditional and the new creation, Pakarena by Andi Siti Nurhani Sapada (Anida) in Makassar, South Sulawesi. The traditional Pakarena is performed primarily for ritual while some parts of this dance are intended to entertain people. Pakarena Anida, meanwhile, is a new creation performed exclusively to entertain people. Both forms are accepted as marker of cultural identity of the Makassar people. In this research, I will argue that Pakarena Anida is a neo-traditional form because it borrows dance elements from the original traditional Pakarena. In analyzing Pakarena Anida as a neo- traditional style, this research utilizes dance history and ethnochoreological approaches.